2001
DOI: 10.1103/physrevb.63.081405
|View full text |Cite
|
Sign up to set email alerts
|

n-alkyl thiol head-group interactions with the Au(111) surface

Abstract: State-of-the-art first principles calculations based on density functional theory were performed on CH 3 (CH 2 ) n−1 S-Au(111) systems. We show that the adsorption site of methylthiolate at low coverage on the Au(111) surface is the fcc site, not the hcp site as has been recently reported. Further, we report results for chain length dependency and the electronic structure of the system.The interaction between organic materials and solid surfaces has been extensively studied because of the broad range of indust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
148
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(172 citation statements)
references
References 51 publications
24
148
0
Order By: Relevance
“…Similarly, Maksymovych et al 47 found a binding energy of −1.77 eV for (b) and a bond length of 2.45 Å for the same adsorption geometry. Masens et al 9 report an adsorption energy of −1.70 eV for (b) close to −1.73 eV found by Yourdshahyan et al 5 In case (c), Zhou and Hagelberg 10 report a dissociative adsorption energy of −0.06 eV, but they conclude that the adsorption of the methanethiol is nondissociative since the nondissociative structure of methanthiol displays a higher adsorption energy than the dissociative one by 0.6 eV. They also found the Au-S bond length to be 2.45 Å.…”
Section: Dissociative Adsorption Of Ch 3 S-sch 3 On Gold Surfacesmentioning
confidence: 86%
See 2 more Smart Citations
“…Similarly, Maksymovych et al 47 found a binding energy of −1.77 eV for (b) and a bond length of 2.45 Å for the same adsorption geometry. Masens et al 9 report an adsorption energy of −1.70 eV for (b) close to −1.73 eV found by Yourdshahyan et al 5 In case (c), Zhou and Hagelberg 10 report a dissociative adsorption energy of −0.06 eV, but they conclude that the adsorption of the methanethiol is nondissociative since the nondissociative structure of methanthiol displays a higher adsorption energy than the dissociative one by 0.6 eV. They also found the Au-S bond length to be 2.45 Å.…”
Section: Dissociative Adsorption Of Ch 3 S-sch 3 On Gold Surfacesmentioning
confidence: 86%
“…Several groups have studied methanethiolate adsorption on Au(111) both experimentally 47 and theoretically. 3,[5][6][7][8][9][10]47 In these studies, the following four reactions are considered: a. dissociative adsorption of CH 3 S-SCH 3 , b. adsorption of CH 3 S radical, c. dissociative adsorption of CH 3 S−H, and d. same as (c), but H is desorbed as H 2 .…”
Section: Dissociative Adsorption Of Ch 3 S-sch 3 On Gold Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…First principles and semi-empirical studies can map the potential energy surface of the gold-thiolate molecular interaction and identify preferred adsorption geometries and binding energies. The literature contains a number of such studies [17] [18][19][20][21], but has generally followed the experimental lead and been confined to the Au(111) surface.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [30] obtained an Au-S bond length of 2.37Å and an Au-S-C bond angle of 102.8 o for the Au-atom-BDT-Au-atom molecule. In comparison, Yourdshahyan, Zhang and Rappe obtained a much larger Au-S-C bond angle between 132° and 138° for the long-chain alkane thiols [CH 3 (CH 2 ) n-1 SH] chemisorbed on the Au(111) surface [59]. The calculated partial densities of states (PDOS) of S and C atoms and the Au atoms that are bonded with the S atoms are shown in Fig.…”
Section: The Structural Model and The First-principles Methods Usedmentioning
confidence: 99%